2019
DOI: 10.4154/gc.2019.06
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of major and trace elements in the Kovin lignite (Serbia)

Abstract: A geochemical and mineralogical study was performed on lignite samples from the Upper Miocene Kovin deposit, hosting three coal seams. The Kovin lignite is characterized by high moisture content, medium to high ash yield, medium to high sulphur content and a relatively low gross and net calorific value. The mineralogical composition, and major and trace element contents were determined by X-ray diffraction, scanning electron microscopy with energy dispersive Xray spectroscopy (SEM-EDS) analyses, and inductivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Such affinity of Si is widely reported from various coals around the World (i.e. Beaton et al, 1991;Crowley et al, 1997;Warwick et al, 1997;Spears, Zheng, 1999;Liu et al, 2001;Zhao et al, 2017Zhao et al, , 2020Finkelman et al, 2019;Životić et al, 2019). Furthermore, Querol et al (1997aQuerol et al ( , b, 2001a, Ward et al (1999), Karayigit et al (2000aKarayigit et al ( , 2020 and Alastuey et al (2001) accept a priori the exclusive relationship of Si with the clay minerals and use the correlation of the element with the alumino-silicate part of the ash to determine its mode of occurrence.…”
Section: Resultsmentioning
confidence: 95%
“…Such affinity of Si is widely reported from various coals around the World (i.e. Beaton et al, 1991;Crowley et al, 1997;Warwick et al, 1997;Spears, Zheng, 1999;Liu et al, 2001;Zhao et al, 2017Zhao et al, , 2020Finkelman et al, 2019;Životić et al, 2019). Furthermore, Querol et al (1997aQuerol et al ( , b, 2001a, Ward et al (1999), Karayigit et al (2000aKarayigit et al ( , 2020 and Alastuey et al (2001) accept a priori the exclusive relationship of Si with the clay minerals and use the correlation of the element with the alumino-silicate part of the ash to determine its mode of occurrence.…”
Section: Resultsmentioning
confidence: 95%
“…Mixed organic/inorganic affinity (Beaton et al, 1991;Querol et al, 1997a;Sutcu, Karayiğit, 2015) or predominant inorganic affinity of Fe (Gluskoter et al, 1977;Querol et al, 1997bQuerol et al, , 2001aLiu et al, 2001;Zhao et al, 2017Zhao et al, , 2020Životić et al, 2019;Karayiğit et al, 2020) are much more readily reported. The research of Querol et al (2001b) on the mode of occurrence of selected elements in coal indicates organic affinity of only ~5-12% of iron.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous authors relate Fe in coal solely to the presence of pyrite (Dill, Wehner, 1999;Ward et al, 1999;Karayiğit et al, 2000a, b;Querol et al, 2001a;Widodo et al, 2010). Iron-rich calcite and dolomite, together with siderite (Kortenski, 1992;Ward, 1992;Bai et al, 2015) or oxides (Životić et al, 2019;Karayiğit et al, 2020), however, can also be recognized as major Fe-bearing minerals in some coals. In addition, contact metamorphism and/or circulation of hydrothermal fluids within the coal seams might also result in increased iron concentrations in coal (Dai et al, 2007;.…”
Section: Resultsmentioning
confidence: 99%
“…Laudal, Benson, Palo, and Addleman (2018) report total lanthanide concentrations in the range 40-400 mg/kg, to be compared with the concentration 56 mg/kg used by Bengtsson 2018. Lower concentrations have however also been reported, (Životić et al, 2019;Adamidou et al, 2007).…”
mentioning
confidence: 87%